Do age and performance status matter? A systematic review and network meta-analysis of immunotherapy studies in untreated advanced/metastatic non-oncogene addicted NSCLC - Siciliano, Maria Anna; d’Apolito, Maria; Del Giudice, Teresa; Caridà, Giulio; Grillone, Francesco; Porzio, Giampiero; Giusti, Raffaele; Tassone, Pierfrancesco; Barbieri, Vito; Tagliaferri, Pierosandro (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) redefined the treatment of non-small cell lung cancer (NSCLC) but their efficacy in elderly and frail patients remains unclear due to immune-senescence and the underrepresentation of these populations in clinical trials. This systematic review and meta-analysis aimed to evaluate and rank first-line ICI-based therapies in NSCLC, stratified by age and performance status (PS).MethodsA comprehensive search for randomized controlled trials (RCTs) of ICI regimens, pairwise and network meta-analyses (NMA) based on age (<65, ≥65, ≥75 years) and PS (0 vs. 1) were conducted. Endpoints were overall survival (OS) and progression-free survival (PFS).ResultsICIs significantly improved OS and PFS versus chemotherapy (CT) in most subgroups. No OS benefit was observed in patients over 75 years. In younger patients, ICI+CT combinations (e.g. pembrolizumab+CT, cemiplimab+CT, camrelizumab+CT) ranked highest for OS and PFS. Among ≥65y patients, cemiplimab ranked first reaching statistical significance in most comparisons, while pembrolizumab was the most effective option for PFS. Stratified by PS, cemiplimab+CT ranked highest for OS in PS 0 patients, whereas cemiplimab was preferred in PS 1 patients. Overall, combination regimens were more effective in younger/fit patients, while monotherapy was more effective in older/PS 1 patients, suggesting a different benefit-risk balance. Anti-PD-1 therapies (alone or in combination) outperformed anti-PD-L1 and anti-CTLA-4 therapies in OS.ConclusionsThis meta-analysis highlights how the efficacy of ICIs in advanced NSCLC varies by age and PS. These findings support a tailored approach to immunotherapy and emphasize the need for trials specifically targeting frail and elderly populations.